Internationalization and hotel performance: The missing pieces. (June 2016) - Assaf, A. George; Josiassen, Alexander; Oh, Haemoon
Few industries are as inherently international as the hotel industry. This article sets out to investigate the impact of internationalization on performance in the hotel industry. Building on the theory of organizational learning the authors test several hypotheses regarding the shape of the internationalization–performance relationship as well as the impact of four moderating variables. In line with the research aim and the underlying dynamism of organizational learning theory, these hypotheses are tested using a dynamic Bayesian model. The results indicate that internationalization has a U-shaped impact on hotel performance, moderated by cultural distance, regulations and restrictions and the level of development congruence. The authors discuss the implications of these findings for practice and provide directions for future research.